GLOBALIZATION CHALLENGES TO UKRAINE’S ECONOMIC SECURITY AND POLICY PRIORITIES TO COUNTER THEM - VASYLTSIV, Taras; KUNYTSKA-ILIASH, Marta (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Increased attention to the issue of ensuring Ukraine’s economic security in the conditions of the intensifying influence of globalization factors, challenges and threats. It is indicated that new globalization challenges determine the need for the formation of new tools and means of ensuring Ukraine’s economic security. The purpose of the study is to identify the globalization challenges to the economic security of Ukraine and justify the policy priorities for countering them. Main directions of the negative impact of globalization threats are determined and, based on them, strategic vectors of the state policy of ensuring the economic security of the national economy are identified. A complex of regulatory tasks and tools has been developed, which serve as guidelines for the formation of an effective and effective system for strengthening the economic security of Ukraine at the current stage of its socio-economic development. The priority areas of counteraction to globalization threats to the economic security of Ukraine are outlined, which define the diversification of foreign economic ties and relations, ensuring the stability of the functioning and independence of the financial system, improving the parameters of the social security system, engaging the "drivers" of economic development, strengthening energy independence and increasing the level of energy efficiency and energy saving , forming a system and ensuring a higher level of functional capacity of critical infrastructure elements, strengthening the functional and structural integration of spatial and territorial economic complexes. The applied value of the research results lies in the further development of the applied provisions of state policy strategizing to ensure the economic security of the state. The scientific novelty of the research results lies in the improvement and clarification of strategic priorities for strengthening the economic security of the state in the conditions of critically acute globalization risks, challenges and threats.